Perbedaan Kemampuan Penalaran Matematis Menggunakan Model Pembelajaran Problem Based Learning dengan Discovery Learning pada Materi Aritmatika Sosial - Tambunan, Listrisnawati; Sinaga, Samuel Juliardi; Hutauruk, Agusmanto J.B (CV. Creative Tugu Pena, 2022)
This study aims to determine whether there are differences in mathematical reasoning abilities between students who use the Problem Based Learning learning model and the Discovery Learning on Social Arithmetic material at Imelda Private Junior High School Medan. The type of research conducted in this study is a quasi-experimental using pre-test and post-test. The population in this study were all seventh grade students of Imelda Private Junior High School Medan which consisted of 3 classes. From this population, the samples of this study were class VII-C and VII-A. Due to the Covid situation, only 15 students were sampled in this study. Based on the results of research and processing, it is concluded that there are differences in the mathematical reasoning abilities of students who use the Problem Based Learning learning model with the Discovery Learning on Social Arithmetic material at Imelda Private Junior High School Medan. Keywords: Mathematical Reasoning Ability, Problem Based Learning, Discovery Learning Model